Flotation of Smithsonite From Quartz Using Pyrophyllite Nanoparticles as the Natural Non-toxic Collector - Pan, Gaochan; Zou, Dan; Wang, Zhen (Frontiers in Chemistry, 2021)
The use of natural hydrophobic mineral nanoparticles as a collector in froth flotation has recently attracted the attention of researchers. In this article, the separation performance and mechanism of pyrophyllite nanoparticles (PNPs) on smithsonite and quartz flotation system were investigated using the method of flotation, zeta potential, contact angle, and scanning electron microscope (SEM)/energy disperse spectroscopy (EDS). The results of single mineral flotation showed that the difference in flotation recovery between smithsonite and quartz was large for NaOL, DDA, and PNP collectors in the acidic pH range, the largest of which was the PNP system. At pH 6, the optimal dosage of PNPs was 1,000 mg/L. Separation of mixed minerals of smithsonite and quartz using a PNP collector provides the optimum concentrate index (Zn grade 50.84% and Zn recovery 85.36%). According to the results of zeta potential measurement, PNPs and quartz were negatively charged, and the surface of smithsonite was positively charged at pH 6. This provided conditions for smithsonite to selectively adsorb PNPs due to different electrostatic forces. Selective adsorption of PNPs in the smithsonite/quartz flotation system was directly observed by SEM/EDS detection. Hydrophobic PNPs were adsorbed on the surface of hydrophilic smithsonite to make it hydrophobic, and the surface of quartz remained hydrophilic. This is the mechanism for separating smithsonite and quartz using PNPs.